Disabling Theological Education. (3rd July 2021) - Conner, Benjamin T.
Abstract: The white male self-sufficient persona that Willie Jennings argues is the evaluative standard for theological education and ministerial formation is also able bodied . Consequently, theological education has been ableist and has neither adequately responded to the reality of disability in its physical or academic structures nor prepared graduates to address the pastoral and theological questions that arise from the lived experience of disability. Theological education needs to be disabled.